Food Web Connectivity in a Mangrove–Seagrass–Patch Reef (MSP) Seascape: Lessons from a Tropical Back-Reef in Puerto Rico - Antonietta Quigg; R. J. David Wells; Jay R. Rooker; Ronald L. Hill; Larissa L. Kitchens; Michael A. Dance; David L. Moulton; Phillip J. Sanchez; Beatrice Padovani Ferreira (Fishes, 2023)
Alterations to the functions and connectivity of mangrove–seagrass–patch reef (MSP) seascapes have the potential to impact the survival, foraging activities, and movement of reef-dependent invertebrates (e.g., crabs and shrimp) and fishes. In the current study, we examined carbon flow in the Guánica Biosphere Reserve in southwestern Puerto Rico using pigment analysis of particulate organic matter and stable isotope analysis of carbon (δ13C) and nitrogen (δ15N) in flora and fauna. Several lines of evidence pointed to N2 fixers (cyanobacteria) being important for fueling primary productivity in this oligotrophic ecosystem including low (

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Report from the conference, ‘identifying obstacles to applying big data in agriculture’ - Emma L. White; J. Alex Thomasson; Brent Auvermann; Newell R. Kitchen; Leland Sandy Pierson; Dana Porter; Craig Baillie; Hendrik Hamann; Gerrit Hoogenboom; Todd Janzen; Rajiv Khosla; James Lowenberg-DeBoer; et al. (Precision Agriculture, 2021)

An individual’s propensity to disperse is dependent on the behavioral type of its peers but not its own behavioral type - Anthony J. Kitchen; David R. Chalcraft (Oecologia, 2020)

A long-term precision agriculture system sustains grain profitability - M. A. Yost; N. R. Kitchen; K. A. Sudduth; R. E. Massey; E. J. Sadler; S. T. Drummond; M. R. Volkmann (Precision Agriculture, 2019)

Reduced Introgression of Sex Chromosome Markers in the Mexican Howler Monkey (Alouatta palliata × A. pigra) Hybrid Zone - Liliana Cortés-Ortiz; Marcella D. Baiz; Javier Hermida-Lagunes; Francisco García-Orduña; Ariadna Rangel-Negrín; Dawn M. Kitchen; Thore J. Bergman; Pedro A. D. Dias; Domingo Canales-Espinosa (International Journal of Primatology, 2019)
Interspecific hybridization allows the introgression or movement of alleles from one genome to another. While some genomic regions freely exchange alleles during hybridization, loci associated with reproductive isolation do not intermix. In many model organisms, the X chromosome displays limited introgression compared to autosomes owing to the presence of multiple loci associated with hybrid sterility or inviability (the “large X-effect”). Similarly, if hybrids are produced, the heterogametic sex is usually inviable or sterile, a pattern known as Haldane’s rule. We analyzed the patterns of introgression of genetic markers located in the mitochondrial (control region) and nuclear (autosomal microsatellites and sex chromosome genes) genomes of two howler monkey species ( Alouatta palliata and A. pigra ) that form a natural hybrid zone in southern Mexico, to evaluate whether the large X-effect and Haldane’s rule affect the outcomes of hybridization between these sister species. To identify the level of admixture of each individual in the hybrid zone ( N = 254) we analyzed individuals sampled outside the hybrid zone (109 A. pigra and 39 A. palliata ) to determine allele frequencies of parental species and estimated a hybrid index based on nuclear markers. We then performed a cline analysis using individuals in the hybrid zone to determine patterns of introgression for each locus. Our analyses show that although the hybrid zone is bimodal (with no known F1 s and few recent generation hybrids) and quite narrow, there has been extensive introgression in both directions, and there is a large array of admixed individuals in the hybrid zone. Mitochondrial and most autosomal markers showed bidirectional introgression, but some had biased introgression toward one species or the other. All markers on the sex chromosomes and a few autosomal markers showed highly restricted introgression. This pattern is consistent with the hypothesis that the sex chromosomes make a disproportionate contribution to reproductive isolation, and our results broaden the taxonomic representation of these patterns across animal taxa.

Temporal but Not Acoustic Plasticity in Hybrid Howler Monkey (Alouatta palliata × A. pigra) Loud Calls - Dawn M. Kitchen; Thore J. Bergman; Pedro A. D. Dias; Lucy Ho; Domingo Canales-Espinosa; Liliana Cortés-Ortiz (International Journal of Primatology, 2019)

Long-term impact of a precision agriculture system on grain crop production - M. A. Yost; N. R. Kitchen; K. A. Sudduth; E. J. Sadler; S. T. Drummond; M. R. Volkmann (Precision Agriculture, 2017)

Occurrence of invasive lionfish (Pterois volitans) larvae in the northern Gulf of Mexico: characterization of dispersal pathways and spawning areas - L. L. Kitchens; C. B. Paris; A. C. Vaz; J. G. Ditty; M. Cornic; J. H. Cowan; J. R. Rooker (Biological Invasions, 2017)

Functional response of U.S. grasslands to the early 21st‐century drought - M. Susan Moran; Guillermo E. Ponce-Campos; Alfredo Huete; Mitchel P. McClaran; Yongguang Zhang; Erik P. Hamerlynck; David J. Augustine; Stacey A. Gunter; Stanley G. Kitchen; Debra P. C. Peters; Patrick J. Starks; Mariano Hernandez (Ecology, 2014)
Grasslands across the United States play a key role in regional livelihood and national food security. Yet, it is still unclear how this important resource will respond to the prolonged warm droughts and more intense rainfall events predicted with climate change. The early 21st‐century drought in the southwestern United States resulted in hydroclimatic conditions that are similar to those expected with future climate change. We investigated the impact of the early 21st‐century drought on aboveground net primary production (ANPP) of six desert and plains grasslands dominated by C 4 (warm season) grasses in terms of significant deviations between observed and expected ANPP. In desert grasslands, drought‐induced grass mortality led to shifts in the functional response to annual total precipitation ( P T ), and in some cases, new species assemblages occurred that included invasive species. In contrast, the ANPP in plains grasslands exhibited a strong linear function of the current‐year P T and the previous‐year ANPP, despite prolonged warm drought. We used these results to disentangle the impacts of interannual total precipitation, intra‐annual precipitation patterns, and grassland abundance on ANPP, and thus generalize the functional response of C 4 grasslands to predicted climate change. This will allow managers to plan for predictable shifts in resources associated with climate change related to fire risk, loss of forage, and ecosystem services.

Scombroid Fishes Provide Novel Insights into the Trait/Rate Associations of Molecular Evolution - Fan Qiu; Andrew Kitchen; J. Gordon Burleigh; Michael M. Miyamoto (Journal of Molecular Evolution, 2014)

Effective serological and molecular screening of deceased tissue donors - A. D. Kitchen; J. A. Newham; H. L. Gillan (Cell and Tissue Banking, 2013)

Male baboon responses to experimental manipulations of loud “wahoo calls”: testing an honest signal of fighting ability - D. M. Kitchen; D. L. Cheney; A. L. Engh; J. Fischer; L. R. Moscovice; R. M. Seyfarth (Behavioral Ecology and Sociobiology, 2013)

Extreme weather and experience influence reproduction in an endangered bird - Brian E. Reichert; Christopher E. Cattau; Robert J. Fletcher; William L. Kendall; Wiley M. Kitchens (Ecology, 2012)
Extreme weather events, such as droughts and heat waves, are expected to become more severe and more frequent in the coming years, and understanding their impacts on demographic rates is of increasing interest to both evolutionary ecologists and conservation practitioners. An individual's breeding probability can be a sensitive indicator of the decision to initiate reproductive behavior under varying environmental conditions, has strong fitness consequences, and can be considered the first step in a life history trade‐off between allocating resources for breeding activities or self‐survival. Using a 14‐year time series spanning large variation in climatic conditions and the entirety of a population's breeding range, we estimated the effects of extreme weather conditions (drought) on the state‐specific probabilities of breeding and survival of an endangered bird, the Florida Snail Kite ( Rostrhamus sociabilis plumbeus ). Our analysis accounted for uncertainty in breeding status assignment, a common source of uncertainty that is often ignored when states are based on field observations. Breeding probabilities in adult kites (>1 year of age) decreased during droughts, whereas the probability of breeding in young kites (1 year of age) tended to increase. Individuals attempting to breed showed no evidence of reduced future survival. Although population viability analyses of this species and other species often implicitly assume that all adults will attempt to breed, we find that breeding probabilities were significantly

Altered Lung Motion is a Sensitive Indicator of Regional Lung Disease - Andreas Fouras; Beth J. Allison; Marcus J. Kitchen; Stephen Dubsky; Jayne Nguyen; Kerry Hourigan; Karen K. W. Siu; Rob A. Lewis; Megan J. Wallace; Stuart B. Hooper (Annals of Biomedical Engineering, 2012)

Population estimates of Alfred mantas (Manta alfredi) in central Maldives atolls: North Male, Ari and Baa - Anne-Marie Kitchen-Wheeler; Csilla Ari; Alasdair J. Edwards (Environmental Biology of Fishes, 2012)

Qualification of serological infectious disease assays for the screening of samples from deceased tissue donors - A. D. Kitchen; J. A. Newham (Cell and Tissue Banking, 2011)

Within-field nitrogen response in corn related to aerial photograph color - J. D. Williams; N. R. Kitchen; P. C. Scharf; W. E. Stevens (Precision Agriculture, 2010)

Annual fire and mowing alter biomass, depth distribution, and C and N content of roots and soil in tallgrass prairie - Duane J. Kitchen; John M. Blair; Mac A. Callaham (Plant and Soil, 2009)

Two classification methods for developing and interpreting productivity zones using site properties - Nicolás Martín; Germán Bollero; Newell R. Kitchen; Alexandra N. Kravchenko; Ken Sudduth; William J. Wiebold; Don Bullock (Plant and Soil, 2006)

From “Snakebites in the new millennium: A state-of-the-art symposium” - J. Audi; S. A. Seifert; J. F. Gennaro; J. W. Skimming; L. H. S. Van Mierop; C. S. Kitchens; M. D. Cardwell; S. P. Bush; R. T. Clark; E. A. Dugan; R. C. Dart; S. R. Rose; et al. (Journal of Medical Toxicology, 2006)

Factors Affecting Reproduction and Mortality Among Baboons in the Okavango Delta, Botswana - D. L. Cheney; R. M. Seyfarth; J. Fischer; J. Beehner; T. Bergman; S. E. Johnson; D. M. Kitchen; R. A Palombit; D. Rendall; J. B. Silk (International Journal of Primatology, 2004)

Differences in native soil ecology associated with invasion of the exotic annual chenopod, Halogeton glomeratus - Jeffrey J. Duda; D. Carl Freeman; John M. Emlen; Jayne Belnap; Stanley G. Kitchen; John C. Zak; Edward Sobek; Mary Tracy; James Montante (Biology and Fertility of Soils, 2003)

Educational Needs of Precision Agriculture - N. R. Kitchen; C. J. Snyder; D. W. Franzen; W. J. Wiebold (Precision Agriculture, 2002)

Influence of an extreme high water event on survival, reproduction, and distribution of Snail Kites in Florida, USA - Robert E. Bennetts; Wiley M. Kitchens; Victoria J. Dreitz (Wetlands, 2002)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Saginaw Gold: A yellow-fleshed potato cultivar with medium-high specific gravity and excellent chip and french fry quality after storage - R. Coffin; R. Chase; N. Thompson; G. Johnston; A. McKeown; M. K. Keenan; D. Craven; R. Kitchen; J. Wilson; R. Y. Yada (American Journal of Potato Research, 1989)